Preserving Alune Language in Neniari Village from Becoming Endangered Language - Pattiasina, Stevany Florence Wendy (Huele: Journal of Applied Linguistics, Literature and Culture, 2021)
The major aim of this study is to comprehend the fact of how Alune can become endangered language in some years later, and to show the role of local agents in micro level to prevent Alune language from becoming endangered and even extinct. The local context of this research is Neniari Village, Maluku Province, Indonesia. The background of this study is based on phenomena in which Alune as the local language in Neniari has been very rare being used by young generation. The data are acquired library study such as journal article and articles on internet, and from observation and interview to children, parents and old people in Neniari. The result shows that historically Alune is the local or indigenous language that used by Alifuru ethnics who lived in Nunusaku mountain, but now it is facing the way to endangerment if the young generation keep reducing use of language in their daily conversation, the parents do not teach their children, and village government do not encourage the use of language in daily conversation. Therefore, local agents such as family, school, village government and even religious institution in Neniari have responsibility to maintain the language for all generations.